Reensilagem e uso de inoculante bacteriano na qualidade de silagem de Sorgo. - Flávia Cristina de Oliveira e Silva (2019)
Silage is the most used forage conservation process in Brazil. The specialization in the production of meat and milk has increased the practice of re-ensiling in Brazil and the world. The purchase of silage from farms specialized in the production of roughage is a common and frequent practice. However, the lack of control and information to regulate this practice still raises doubts among producers at the time of acquisition. When the silage is relocated there is an aerobic exposure of the material. The exposure allows the growth of microorganisms such as yeasts and mold that cause deterioration of the silage, which can compromise the quality and nutritional value. To solve this problem, the microbial inoculants use in green material is increasing frequently, with the objective of improve the silage aerobic stability. The objective of this study was to determine the effect of re-ensiling after 48 hours and microbial inoculant use on the quality of sorghum silages. The losses of gases (+ 8%) and effluents (+ 50%) were higher in the re-ensiled silages (P <0.05). Thus, the total losses were 17% higher than in conventional silage. The re-ensiling reduced the aerobic stability of the silages (P <0.05) in 3.8 days, and increased the mold count in silages with and without inoculant, 2.13x105 and 4.16x103 CFU.g-1 of green mass (GM), respectively. The use of inoculant reduced the pH of the silages to 5% (P <0.05). The re-ensiling increased the silages pH by an average of 5.5% (P <0.05). The concentrations of N-NH3.NT-1 were reduced in silages inoculated (18.34%) and higher in silages re-ensiled (28.88%). The re-ensiling after 48 hours did not affect the quality of sorghum silages. The use of inoculants in the sorghum silages re-ensiled did not improve the quality of the material.